Digital Charting and Outlining Note-taking Types on Memory Retention: A Within-Subjects Experimental Study Among University Students - Nurul Wardhani; Zahra Amira Athaya; Athena Rossa Widiantari; Vhildza Desyana; Safira Azzahra Putri; Nadhira Nur Rahman (Kajian Psikologi dan Kesehatan Mental, 2025)
Purpose: This study examined whether digital charting and outlining note-taking methods differ in their effects on immediate memory retention among undergraduate psychology students at Universitas Padjadjaran.Research Methodology: A within-subjects experimental design involved 108 psychology students from the 2022 and 2023 cohorts. Participants completed two note taking conditions charting and outlining presented online via Zoom for seven minutes each. Immediate memory retention was measured using separate 10 item multiple choice quizzes administered through Google Forms. Data were analyzed using the Kruskal Wallis test due to non normal distribution.Results: No significant difference was found between charting and outlining note taking methods in immediate memory retention (p > .05). Both conditions produced high levels of accuracy, with mean scores of 84.8% for charting and 80.6% for outlining. Variations in performance were observed across individual items, suggesting differences in item difficulty rather than note taking format effects.Conclusions: Digital charting and outlining methods showed equivalent effectiveness in supporting short term memory retention when learning duration and content exposure were controlled.Limitations: Findings were limited by online implementation, non equivalent learning materials, the absence of a control group, and uncontrolled individual factors such as attention and motivation.Contributions: This study provides evidence on digital note taking practices in Indonesian higher education and offers guidance for students selecting note-taking strategies in online learning environments.